2020
DOI: 10.3390/antiox9060560
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Rich Fibrin Can Neutralize Hydrogen Peroxide-Induced Cell Death in Gingival Fibroblasts

Abstract: Hydrogen peroxide is a damage signal at sites of chronic inflammation. The question arises whether platelet-rich fibrin (PRF), platelet-poor plasma (PPP), and the buffy coat can neutralize hydrogen peroxide toxicity and thereby counteract local oxidative stress. In the present study, gingival fibroblasts cells were exposed to hydrogen peroxide with and without lysates obtained from PRF membranes, PPP, heated PPP (75 °C for 10 min), and the buffy coat. Cell viability was examined by trypan blue staining, live-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 40 publications
(71 reference statements)
2
16
0
Order By: Relevance
“…Conversely, lysates of heated PPP, similar to the red blood cell fraction, failed to provoke the expression of the TGF-β target genes and the activation of upstream signaling consisting of activation of the TGF-β receptor 1 kinase [32], as well as the phosphorylation and nuclear translocation of Smad2/3 [33]. This finding is in line with the catalase activity of PRF lysates that is abolished by heating [21]. There were variations among the blood and cell donors but the overall finding that PPP has a weaker TGF-β activity than buffy coat was consistent among all experiments.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Conversely, lysates of heated PPP, similar to the red blood cell fraction, failed to provoke the expression of the TGF-β target genes and the activation of upstream signaling consisting of activation of the TGF-β receptor 1 kinase [32], as well as the phosphorylation and nuclear translocation of Smad2/3 [33]. This finding is in line with the catalase activity of PRF lysates that is abolished by heating [21]. There were variations among the blood and cell donors but the overall finding that PPP has a weaker TGF-β activity than buffy coat was consistent among all experiments.…”
Section: Discussionsupporting
confidence: 67%
“…Heating, however, not only inactivates plasminogen and coagulates albumin; it might also affect the activity of the catalase [21] and growth factors intrinsic to the PRF clot. We recently performed a proteomic analysis combined with a whole genome gene array of a traditional PRF membrane and identified that TGF-β was a major growth factor with respect to its activation of genes in oral fibroblasts [22].…”
Section: Introductionmentioning
confidence: 99%
“…The 3T3-L1 pre-adipocyte mesenchymal cells are an established model for adipogenesis, also used for inflammation research [ 42 ]. Gingival fibroblasts are a widely used model for the investigation of inflammation of the oral cavity and oral disease [ 43 ] and have been utilized in PRF research [ 44 , 45 ]. The goal of the present study was to take advantage of the ST2 and 3T3-L1 cells and gingival fibroblasts to study the possible anti-inflammatory activity of the various PRF preparations in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…After removing the serum, we obtained a white clot. This procedure is similar to our previously protocol used to prepare PRF membranes [ 18 , 19 , 20 ]. The clotted fraction before and after removing the serum by a gauze was used to measure the wet weight and dry weight, respectively.…”
Section: Methodsmentioning
confidence: 99%